Assessment of the correlates of respiratory morbidity related quality of life, using St George Respiratory Questionnaire (SGRQ) among male COPD patients - Dogra, Vikas; Menon, Balakrishnan; Bansal, Vishal; Gaur, Shailendra Nath (International Journal of Advances in Medicine, 2018)
Background: COPD is ranked eighth among the top 20 conditions causing disability globally. Assessment in subjective areas such as dyspnea and HRQL provides complementary information to physiologic measurements. Lower Health-Related Quality of Life has been associated with mortality and morbidity in COPD. Methods: The study was conducted at the Department of Respiratory Medicine and at Vallabhbhai Patel Chest Institute and the associated, Vishwanathan Chest Hospital, University of Delhi. Between September 2012 to August 2013. We conducted present study on 40 male COPD subjects aged more than 45 years, divided into 4 groups based on CT phenotype as normal, Airway Dominant (AD), Emphysema Dominant (ED) and mixed types. We compared the St. George Respiratory Questionnaire scores, 6 Minutes’ walk Distance scores, Clinical parameters, Spirometry indices across these phenotypes. Results: The mean SGRQ score in present study was 54.07 ± 17.24 (Range :17.3 to 84.57). The Mean 6MWD in present study was 434.58 ± 125.47 metres. The significant parameters which had correlation with SGRQ total score were Age (r=0.343, p = 0.03), 6MWD (-0.397, p = 0.011), FEV1 /FVC (0.499, p< 0.001), DLCO (-0.601, p <0.001), Low attenuation areas in CT (0.606, p< 0.001). Conclusions: 6MWD, FEV1/FVC, age, Low attenuation areas in CT, DLCO had an influence on the quality of life as measured by SGRQ scores in present study. Therapeutic approaches to improve the quality of life in COPD should take these indices into consideration.